Enhancing biology education students ability to solve problems in environmental science material through inquiri model-based lesson study - Rita Istiana; M. Taufik Awaludin (Biosfer: Jurnal Pendidikan Biologi, 2018)
This study was an action research which applied lesson study in its learning process. The aim of the study was to improve students’ ability to solve various environmental problems, especially for population problems in the Environmental Study Course by applying inquiry model. The study was conducted in October 2016 to January 2017 and involved students of Biology Education as the analysis unit, in the Faculty of Teacher Training and Education, Universitas Pakuan. Research procedures composed of three steps: design (plan), action (do), observation and reflection (see) which consist of two cycles. The result showed that inquiry model based lesson study could improve students’ ability to solve environmental problems, especially for the population. Enhancement of problem-solving ability was implemented in the result of the first cycle with a class average of 77,63 and a completeness percentage 63,33%. It was increased in the second cycle with a class average of 84,45 and a completeness percentage 86,67%.